1968
DOI: 10.1002/jsfa.2740191003
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of the retrogradation of gelatinised starch

Abstract: A method was developed for the study of starch retrogradation by differential thermal analysis. The kinetics of the crystallisation process were studied using the expression 8 = exp (-ktn), where 8 = the fraction of crystallisable starch remaining uncrystallised at time t. The values for the Avrami exponent (n) and the rate constant ( k ) were found to coincide with values previously obtained for the staling of bread, as followed by measurement of crumb elastic modulus. No difference between the time constants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

1969
1969
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(59 citation statements)
references
References 5 publications
3
56
0
Order By: Relevance
“…The branched chains of starch remain in the granules during baking and link together slowly during storage to make the crumb progressively more firm with time (Angioloni and Collar 2009). Previous studies reported n to be unity suggesting starch crystallization to be an instantaneous nucleation process followed by linear growth of crystals (Kim and D'Appolonia 1977;MacIver 1969). However, recent publications (Armero and Collar 1998;Martin et al 1991) showed that Avrami exponent was different to one suggesting the fact that bread staling is the result of several effects and starch retrogradation is not the only cause (Zobel and Kulp 1996).…”
Section: Crumb Firming Kineticsmentioning
confidence: 86%
“…The branched chains of starch remain in the granules during baking and link together slowly during storage to make the crumb progressively more firm with time (Angioloni and Collar 2009). Previous studies reported n to be unity suggesting starch crystallization to be an instantaneous nucleation process followed by linear growth of crystals (Kim and D'Appolonia 1977;MacIver 1969). However, recent publications (Armero and Collar 1998;Martin et al 1991) showed that Avrami exponent was different to one suggesting the fact that bread staling is the result of several effects and starch retrogradation is not the only cause (Zobel and Kulp 1996).…”
Section: Crumb Firming Kineticsmentioning
confidence: 86%
“…Several previous studies using the Avrami model have concluded that the exponent n in Eq. 1 is unity and the basic mechanism for starch crystallization is instantaneous nucleation followed by linear growth of crystals [29,30]. Nevertheless, other publications [11,31,32] showed that Avrami exponent was different to one.…”
Section: Effect Of Enzyme Treatment On Bread Shelf Lifementioning
confidence: 94%
“…Analysis of retrogradation rate: The Avrami model was used to describe the kinetics of starch recrystallization. The model (McIver, Axford, Colwell, & Elton, 1968) can be expressed as…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%